Agrobacterium‐mediated inoculation of asymptomatic Apple latent spherical virus as gene silencing vector in pea (Pisum sativum L.). Issue 1 (29th November 2019) - Xiong, Ruyi; Pajak, Aga; Wang, Aiming; Yoshikawa, Nobuyuki; Marsolais, Frédéric; Todd, Christopher D.
Abstract: Apple latent spherical virus (ALSV) has been developed into a virus‐induced gene silencing vector with a broad host range, including legumes. Using Agrobacterium tumefaciens, delivered via stem injection, we introduced ALSV vectors carrying a phytoene desaturase ( PDS ) sequence from Phaseolus vulgaris, resulting in highly uniform knockdown phenotypes on Pisum sativum L., 23 days postinoculation. The infection rate ranged from 7.6% to 36.3% on five different P. sativum varieties using Agrobacterium stem inoculation. Mechanical inoculation using infected pea sap improved the infection rates to 80% on P. sativum cultivar AAC Lacombe. Reverse transcription polymerase chain reaction and real‐time reverse transcription polymerase chain reaction demonstrated that ALSV virus RNA accumulated in roots, tendrils and leaves, accompanied by decreased PsPDS (Pisum sativum phytoene desaturase) expression level. ALSV virus RNA was also detected from sepals, petals, carpels, pods, and seed coats but not in embryos. This method simplifies the ALSV inoculation and improves the use of ALSV vectors for functional genomics in P. sativum.